Modified Immunoscore Improves Prediction of Survival Outcomes in Patients Undergoing Radical Cystectomy for Bladder Cancer—A Retrospective Digital Pathology Study - Uwe Bieri; Lorenz Buser; Marian Severin Wettstein; Daniel Eberli; Karim Saba; Holger Moch; Thomas Hermanns; Cédric Poyet (Diagnostics, 2022)
To evaluate the prognostic value of a modified Immunoscore (mIS) in a cohort of bladder cancer (BC) patients undergoing radical cystectomy (RC), two tissue microarrays of 159 BC patients were immunohistochemically stained for CD3/CD8/FOXP3 and CD45RO to detect Tumor-Infiltrating Lymphocytes (TIL). To predict progression free survival (PFS) and cancer specific survival (CSS), a predictive model cumulatively incorporating all four components was constructed and labeled as mIS. Patients were stratified into two risk groups; “high mIS/favorable risk” and “low mIS/unfavorable risk”. Kaplan–Meier analysis was used to test mIS within each American Joint Committee on Cancer (AJCC) stage group for BC. In a univariable cox regression analysis all single components used for mIS, showed a significant association with CSS. Patients with high mIS (all components) in the AJCC stage IIIa group additionally showed a significantly longer PFS (Hazard Ratio (HR): 2.7; p = 0.008) and CSS (HR: 3.5; p = 0.006) as compared to patients with low mIS. mIS is of prognostic value in BC patients undergoing RC and was able to stratify patients within AJCC stage IIIa and might thus serve as a prognostic marker to guide risk-adapted treatment or follow-up strategies after RC.